Anti-UV color master batch for guideboard reflective film and preparation method of anti-UV color master batch

By introducing yttrium zinc oxide and modified yttrium zinc oxide into the masterbatch of the street sign reflective film, and using isoleucine and sodium benzoate to regulate its morphology, the existing masterbatch is solved inadequate anti-ultraviolet and anti-oxidation performance. The problem of this problem is to achieve higher UV resistance, mechanical properties and light transmittance.

CN119490719APending Publication Date: 2025-02-21SHENZHEN JINZHICHENG PLASTIC TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411716448.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The masterbatches of existing street sign reflective films have poor UV resistance and oxidation resistance, and cannot guarantee stability during processing and outdoor use.

Method used

Using mass percentages including 10% to 20% yttrium doped zinc oxide or modified yttrium doped zinc oxide, 2% to 5% dispersant, 2% to 5% anti-ultraviolet agent, 0.5% to 1% anti-anti- The oxidant, the remaining material is a masterbatch of PMMA resin. It prepares yttrium zinc oxide through hydrothermal reaction, and uses isoleucine and sodium benzoate to regulate its morphology.

Benefits of technology

The masterbatch's resistance to UV, mechanical properties and light transmittance are improved, and the stability and safety of street sign reflective films are ensured in outdoor use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490719A_ABST
    Figure CN119490719A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-UV color master batch for a reflective film of a guideboard and a preparation method of the anti-UV color master batch. The color master batch comprises the following components in percentage by mass: 10%-20% of yttrium-doped zinc oxide or modified yttrium-doped zinc oxide, 2%-5% of a dispersing agent, 2%-5% of an anti-ultraviolet agent, 0.5%-1% of an antioxidant and the balance of PMMA (Polymethyl Methacrylate) resin. The yttrium element is introduced into the zinc oxide, and the isoleucine and the sodium benzoate are used for regulating and controlling the morphology of the zinc oxide, so that not only is the ultraviolet shielding performance of the zinc oxide improved, but also the light transmittance can be improved by adding the modified zinc oxide into the color master batch. The anti-UV color master batch for the guideboard reflective film has the advantages of high mechanical strength, good ultraviolet resistance and good light transmission, meanwhile, the preparation method is simple, the raw materials are cheap and easy to obtain, and the anti-UV color master batch has a very good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of masterbatches, and in particular to an anti-UV masterbatch for a road sign reflective film and a preparation method thereof. Background Art

[0002] Road sign reflective film is a safety protection product made of reflective material. It can produce a strong reflective effect under the illumination of light, providing safety for vehicles, pedestrians and night workers in the dark. This reflective film can provide high visibility at night or in low-light environments through the retro-reflective principle of high-refractive index materials, ensuring that traffic signs are clearly visible. Masterbatch, also called color species, is a plastic colorant made of a high proportion of pigments or additives and thermoplastic resins that are well dispersed. When processing and making road sign reflective film, compared with directly adding pigments, the use of masterbatch can improve the dispersion and tinting power of the pigments and improve the coloring stability of the road sign reflective film.

[0003] Polymethyl methacrylate (PMMA), also known as acrylic or organic glass, has the advantages of high transparency, low price, and easy mechanical processing. Traditional PMMA masterbatch is composed of pigments, PMMA and additives, and its UV resistance and antioxidant properties are poor, and it cannot guarantee the stability of road sign reflective film during processing and outdoor use. There are also some methods that have made relevant improvements. For example, CN116041883A discloses a micro-nano laminated PMMA / nano ZnO composite material and a preparation method thereof. The composite material includes 95% to 99% PMMA and 1% to 5% modified nano ZnO by mass percentage, and mainly prepares PMMA composite materials with high UV absorption rate by micro-nano laminated co-extrusion. However, this method has relatively precise equipment requirements, and the micro-nano laminated process is difficult to master. At the same time, the amount of pigment ZnO added is low, and the coloring ability is not strong. CN110903587A discloses a highly transparent and aging-resistant PMMA color masterbatch and a preparation method, wherein the masterbatch includes phthalocyanine green 8%, phthalocyanine red 8%, titanium dioxide 8%, iron oxide yellow 8%, PMMA 43%, dispersant 10%, additive 10% and stearate 5% by mass percentage, wherein the additive is flame retardant 40% and antioxidant 60%. This masterbatch has good stability, however, the dispersant and additive account for up to 20%, which increases the cost.

[0004] It is necessary to provide masterbatches with high UV resistance, strong coloring properties and good mechanical properties. Summary of the invention

[0005] In order to overcome the problems existing in the prior art, the present invention provides an anti-UV masterbatch for road sign reflective film, which comprises, by mass percentage, 10%~20% yttrium-doped zinc oxide or modified yttrium-doped zinc oxide, 2%~5% dispersant, 2%~5% anti-ultraviolet agent, 0.5%~1% antioxidant, and the remainder is PMMA resin.

[0006] Furthermore, the preparation method of the yttrium-doped zinc oxide comprises, by weight, 2-5 parts of a soluble zinc salt, 0.1-0.3 parts of a soluble yttrium salt and 50-100 parts of a solvent are mixed, the pH is adjusted, and then a hydrothermal reaction is performed to obtain yttrium-doped zinc oxide.

[0007] It should be noted that in the present invention, the types of soluble zinc salt and soluble yttrium salt do not need to be strictly limited, and can be conventionally obtained. For example, the soluble zinc salt can be selected from at least one of zinc nitrate hexahydrate, zinc acetate dihydrate, zinc chloride, etc.; the soluble yttrium salt can be yttrium nitrate hexahydrate, yttrium chloride hexahydrate, etc.

[0008] Furthermore, the preparation method of the modified yttrium-doped zinc oxide comprises, by weight, 2-5 parts of soluble zinc salt, 0.1-0.3 parts of soluble yttrium salt, 0.5-1 parts of isoleucine and 50-100 parts of solvent are mixed, pH is adjusted, and then a hydrothermal reaction is performed to obtain modified yttrium-doped zinc oxide.

[0009] Furthermore, 0.1 to 0.3 parts of sodium benzoate are added when isoleucine is added.

[0010] Further, the solvent includes at least one of water, ethanol, acetone, isopropanol, and ethylene glycol; Furthermore, the pH is adjusted to 11.0 to 13.0. The substance used to adjust the pH in the present invention does not need to be strictly limited, and can be sodium hydroxide, potassium hydroxide, etc.

[0011] Furthermore, the hydrothermal reaction is continued at 130-180° C. for 8-12 h.

[0012] Zinc oxide is known for its unique white appearance. It is not only pure in color, but also has a high refractive index and scattering ability. At the same time, zinc oxide can transfer the energy of ultraviolet rays and scatter them in different directions. As an N-type semiconductor, the electrons in the valence band can accept the energy in the ultraviolet rays and undergo transitions. The scattering and absorption of ultraviolet rays by zinc oxide makes it not only a white pigment, but also a UV shielding agent. The ultraviolet shielding performance of zinc oxide is largely related to its structure and size. At the same time, element doping can improve the conductivity and lattice stability of zinc oxide, thereby further improving the ultraviolet shielding performance. The present invention introduces yttrium into zinc oxide, and uses isoleucine and sodium benzoate to regulate the morphology of zinc oxide, which not only improves the ultraviolet shielding performance of zinc oxide, but also improves the light transmittance of the modified zinc oxide added to the masterbatch.

[0013] Generally speaking, the higher the pigment content in the masterbatch, the more difficult it is to disperse. Dispersants are a very important component in the preparation of masterbatches. Their main function is to wet the pigment so that the pigment can be evenly dispersed in the resin and no longer agglomerate during the processing. The selection of dispersants needs to have good compatibility with the resin, not affect the quality of the colored product, and generally have a lower melting point than the resin, and have good affinity with the pigment.

[0014] Furthermore, the dispersant includes at least one of polyethylene wax, diffusion oil, talcum powder and ammonium stearate.

[0015] The anti-ultraviolet agent gives the masterbatch anti-ultraviolet properties, so that adding the masterbatch to the plastic can improve the plastic's anti-ultraviolet properties; the antioxidant gives the masterbatch antioxidant properties, so that adding the masterbatch to the plastic can improve the plastic's antioxidant properties.

[0016] Furthermore, the anti-ultraviolet agent includes at least one of a benzophenone anti-ultraviolet agent, a hindered benzoate anti-ultraviolet agent, and a benzotriazole anti-ultraviolet agent.

[0017] Furthermore, the antioxidant includes at least one of a hindered phenol antioxidant and a phosphite antioxidant.

[0018] The present invention also provides a method for preparing the above-mentioned UV-resistant masterbatch for road sign reflective film, comprising: The PMMA resin is heated and melted, and then yttrium-doped zinc oxide or modified yttrium-doped zinc oxide and a dispersant are added, mixed and stirred to obtain a mixture; Add an anti-ultraviolet agent and an antioxidant into the mixture, mix and stir, and then extrude and granulate to obtain an anti-UV masterbatch for road sign reflective film.

[0019] Compared with the prior art, the present invention has the following beneficial effects: The present invention introduces yttrium into zinc oxide, and uses isoleucine and sodium benzoate to regulate the morphology of zinc oxide, which not only improves the ultraviolet shielding performance of zinc oxide, but also improves the light transmittance when the modified zinc oxide is added to the masterbatch. The anti-UV masterbatch for the road sign reflective film of the present invention has the advantages of high mechanical strength, good ultraviolet resistance and good light transmittance, and the preparation method is simple, the raw materials are cheap and easy to obtain, and has a good application prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A scanning electron microscope image of zinc oxide prepared in Comparative Example 1 is shown; Figure 2 shows a scanning electron microscope image of zinc oxide prepared in Example 1; Figure 3 shows a scanning electron microscope image of zinc oxide prepared in Example 2; Figure 4 A scanning electron microscope image of zinc oxide prepared in Example 3 is shown. DETAILED DESCRIPTION

[0021] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0022] Some of the raw materials used in the embodiments of the present invention are described as follows: Polyethylene wax, model Q-400, purchased from Shandong Baolilai Plastic Additives Co., Ltd.; Benzophenone anti-ultraviolet agent, model UV-531, purchased from Changzhou Youfeng Chemical Co., Ltd.; hindered benzoate anti-ultraviolet agent, model UV-2908, purchased from Guangzhou Si Tuyuan Chemical Co., Ltd.; in the examples, model UV-531 and model UV-2908 are used as the abbreviations of the selected benzophenone anti-ultraviolet agent and hindered benzoate anti-ultraviolet agent; Hindered phenol antioxidant, model 1010, purchased from BASF (China) Co., Ltd.; PMMA resin, brand VH001, was purchased from Mitsubishi Rayon Polymer Materials (Nantong) Co., Ltd.; Isoleucine; product number HNHUAYUE0527, purchased from Guangzhou Jiahang Biotechnology Co., Ltd.; Sodium benzoate, brand number 208-534-8, was purchased from Shandong Pingju Biotechnology Co., Ltd.

[0023] Other raw materials not mentioned are common raw materials in the art. The above content is only to help illustrate the present invention and should not be construed as a strict limitation of the present invention. Those skilled in the art can directly purchase or prepare the same / similar raw materials from the market. These contents will not be repeated in the examples.

[0024] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1 A method for preparing UV-resistant masterbatch for road sign reflective film. S1. Weigh the raw materials by mass percentage: 15% yttrium-doped zinc oxide, 3% polyethylene wax, 3% UV-531, 1% UV-2908, 1% hindered phenol antioxidant, and 77% PMMA resin; S2, heating and melting PMMA resin at 175° C., then adding yttrium-doped zinc oxide and polyethylene wax, and mixing and stirring at 80 rpm for 15 minutes to obtain a mixture; S3. Add UV-531, UV-2908 and hindered phenol antioxidant into the mixture, mix and stir at 50 rpm for 20 minutes, and then extrude and granulate to obtain anti-UV masterbatch for road sign reflective film.

[0026] Wherein, the preparation method of yttrium-doped zinc oxide is: 40 g of zinc acetate dihydrate, 2 g of yttrium nitrate hexahydrate and 800 g of water were stirred at 300 rpm for 15 min, and then the pH was adjusted to 12.5 with sodium hydroxide; then the mixture was transferred to a reactor and subjected to a hydrothermal reaction at 175°C for 9 h; after the reaction, the mixture was naturally cooled to room temperature, the insoluble matter was collected by filtration and washed three times with water and ethanol respectively, and then dried in a constant temperature oven at 120°C for 12 h, and then calcined in an air atmosphere muffle furnace at 450°C for 2 h to obtain yttrium-doped zinc oxide.

[0027] Example 2 A method for preparing UV-resistant masterbatch for road sign reflective film. S1. Weigh the raw materials by mass percentage: 15% modified yttrium-doped zinc oxide, 3% polyethylene wax, 3% UV-531, 1% UV-2908, 1% hindered phenol antioxidant, and 77% PMMA resin; S2, heating and melting PMMA resin at 175° C., then adding modified yttrium-doped zinc oxide and polyethylene wax, and mixing and stirring at 80 rpm for 15 min to obtain a mixture; S3. Add UV-531, UV-2908 and hindered phenol antioxidant into the mixture, mix and stir at 50 rpm for 20 minutes, and then extrude and granulate to obtain anti-UV masterbatch for road sign reflective film.

[0028] Wherein, the preparation method of modified yttrium-doped zinc oxide is: 40 g of zinc acetate dihydrate, 2 g of yttrium nitrate hexahydrate, 6 g of isoleucine and 800 g of water were stirred at 300 rpm for 15 min, and then the pH was adjusted to 12.5 with sodium hydroxide; then the mixture was transferred to a reactor and hydrothermally reacted at 175°C for 9 h; after the reaction, the mixture was naturally cooled to room temperature, the insoluble matter was collected by filtration and washed three times with water and ethanol respectively, and then dried in a constant temperature oven at 120°C for 12 h, and then calcined in an air atmosphere muffle furnace at 450°C for 2 h to obtain modified yttrium-doped zinc oxide.

[0029] Example 3 A method for preparing UV-resistant masterbatch for road sign reflective film. S1. Weigh the raw materials by mass percentage: 15% modified yttrium-doped zinc oxide, 3% polyethylene wax, 3% UV-531, 1% UV-2908, 1% hindered phenol antioxidant, and 77% PMMA resin; S2, heating and melting PMMA resin at 175° C., then adding modified yttrium-doped zinc oxide and polyethylene wax, and mixing and stirring at 80 rpm for 15 minutes to obtain a mixture; S3. Add UV-531, UV-2908 and hindered phenol antioxidant into the mixture, mix and stir at 50 rpm for 20 minutes, and then extrude and granulate to obtain anti-UV masterbatch for road sign reflective film.

[0030] Wherein, the preparation method of modified yttrium-doped zinc oxide is: 40g zinc acetate dihydrate, 2g yttrium nitrate hexahydrate, 6g isoleucine, 2g sodium benzoate and 800g water were stirred at 300rpm for 15min, and then the pH was adjusted to 12.5 with sodium hydroxide; then the mixture was transferred to a reactor and hydrothermally reacted at 175°C for 9h; after the reaction, the mixture was naturally cooled to room temperature, the insoluble matter was collected by filtration and washed three times with water and ethanol respectively, and then dried in a constant temperature oven at 120°C for 12h, and then calcined in an air atmosphere muffle furnace at 450°C for 2h to obtain modified yttrium-doped zinc oxide.

[0031] Comparative Example 1 A method for preparing UV-resistant masterbatch for road sign reflective film. S1. Weigh the raw materials by mass percentage: 15% zinc oxide, 3% polyethylene wax, 3% UV-531, 1% UV-2908, 1% hindered phenol antioxidant, and 77% PMMA resin; S2, heating and melting PMMA resin at 175° C., then adding zinc oxide and polyethylene wax, and mixing and stirring at 80 rpm for 15 min to obtain a mixture; S3. Add UV-531, UV-2908 and hindered phenol antioxidant into the mixture, mix and stir at 50 rpm for 20 minutes, and then extrude and granulate to obtain anti-UV masterbatch for road sign reflective film.

[0032] Wherein, the preparation method of zinc oxide is: 40 g of zinc acetate dihydrate and 800 g of water were stirred at 300 rpm for 15 min, and then the pH was adjusted to 12.5 with sodium hydroxide; then the mixture was transferred to a reactor and subjected to a hydrothermal reaction at 175°C for 9 h; after the reaction, the mixture was naturally cooled to room temperature, the insoluble matter was collected by filtration and washed three times with water and ethanol respectively, and then dried in a constant temperature oven at 120°C for 12 h, and then calcined in an air atmosphere muffle furnace at 450°C for 2 h to obtain yttrium-doped zinc oxide.

[0033] Comparative Example 2 A method for preparing UV-resistant masterbatch for road sign reflective film. S1. Weigh the raw materials by mass percentage: 15% modified zinc oxide, 3% polyethylene wax, 3% UV-531, 1% UV-2908, 1% hindered phenol antioxidant, and 77% PMMA resin; S2, heating and melting PMMA resin at 175° C., then adding modified zinc oxide and polyethylene wax, and mixing and stirring at 80 rpm for 15 minutes to obtain a mixture; S3. Add UV-531, UV-2908 and hindered phenol antioxidant into the mixture, mix and stir at 50 rpm for 20 minutes, and then extrude and granulate to obtain anti-UV masterbatch for road sign reflective film.

[0034] Wherein, the preparation method of modified zinc oxide is: 40 g of zinc acetate dihydrate, 6 g of isoleucine, 2 g of sodium benzoate and 800 g of water were stirred at 300 rpm for 15 min, and then the pH was adjusted to 12.5 with sodium hydroxide; then the mixture was transferred to a reactor and subjected to a hydrothermal reaction at 175°C for 9 h; after the reaction, the mixture was naturally cooled to room temperature, the insoluble matter was collected by filtration and washed three times with water and ethanol respectively, and then dried in a constant temperature oven at 120°C for 12 h, and then calcined in an air atmosphere muffle furnace at 450°C for 2 h to obtain modified zinc oxide.

[0035] Comparative Example 3 A method for preparing an anti-UV masterbatch. S1. Weigh the raw materials by mass percentage: 3% polyethylene wax, 3% UV-531, 1% UV-2908, 1% hindered phenol antioxidant, and 92% PMMA resin; S2, heating and melting PMMA resin at 175° C., then adding polyethylene wax, and mixing and stirring at 80 rpm for 15 min to obtain a mixture; S3. Add UV-531, UV-2908 and hindered phenol antioxidant into the mixture, mix and stir at 50 rpm for 20 minutes, and then extrude and granulate to obtain UV-resistant masterbatch.

[0036] Test Case The performance of zinc oxide is closely related to its morphology and element doping. The microstructure of the zinc oxide materials prepared in the examples and comparative examples was observed using a scanning electron microscope. Figure 1 It can be seen that the zinc oxide prepared in Comparative Example 1 is a prism structure with a width of about 300-800 nm and a length of about 5-20 μm; Figure 2 The structure of the yttrium-doped zinc oxide prepared in Example 1 is similar to that of zinc oxide, but its dispersibility is poor, and there is uneven agglomeration on the outer surface of the yttrium-doped zinc oxide; the modified yttrium-doped zinc oxide ( Figure 3 ), isoleucine was introduced into the hydrothermal reaction, so that the dispersibility of yttrium-doped zinc oxide was enhanced, and the surface agglomeration was significantly reduced, and the overall prismatic structure was still present, and the size did not change significantly; it is worth noting that the modified yttrium-doped zinc oxide ( Figure 4 ), whose morphology evolves from a prismatic structure to a flower-like shape. It can also be seen that the overall structure is composed of prisms with a width of about 100~300nm and a length of about 5-20μm, and there is almost no agglomeration on the surface. This is because isoleucine and sodium benzoate can effectively regulate the early morphology of zinc species in the presence of yttrium, causing the zinc species to decrease in size and grow divergently along the nucleation center.

[0037] The impact strength, light transmittance and haze of the masterbatch of the embodiment and the comparative example were tested respectively with reference to the standards GB / T 1843-2008 "Test for notched impact strength of plastics" and GB / T 2410-2008 "Determination of light transmittance and haze of transparent plastics". The results are shown in Table 1.

[0038] Table 1 Impact strength, transmittance and haze test results of masterbatch Impact strength (KJ / m2) Light transmittance (%) Haze (%) Example 1 1.9 85 93 Example 2 2.2 90 95 Example 3 2.3 91 96 Comparative Example 1 2.1 90 96 Comparative Example 2 2.3 92 97 Comparative Example 3 2.5 93 98 From the test results of Table 1, it can be seen that the comparative example 3 without the introduction of yttrium-doped zinc oxide and modified yttrium-doped zinc oxide exhibits the strongest impact strength, light transmittance and haze. This is because the introduction of inorganic material yttrium-doped zinc oxide and modified yttrium-doped zinc oxide on the basis of other formulas will make the PMMA resin non-uniform, causing a decrease in strength and light transmittance. The various properties of Example 1 are also reduced compared with those of Comparative Example 1, which is caused by the poor dispersibility of yttrium-doped zinc oxide in PMMA resin. Compared with Example 1, the impact strength, light transmittance and haze of Example 2 and Example 3 are improved, which is because the morphology of modified yttrium-doped zinc oxide is significantly improved, making the modified yttrium-doped zinc oxide more compatible with PMMA resin. Overall, the performance of the masterbatch prepared in Example 2 and Example 3 is not significantly reduced compared with that of Comparative Example 3 without the addition of pigment, which is sufficient to meet the needs of use.

[0039] The masterbatch of the embodiment and the comparative example was irradiated at a wavelength of 315-400 nm and a light intensity of 6000 μw / cm 2 After exposure to ultraviolet light for 30 days, the elongation at break retention rate of the test material was measured according to the standard GB / T 1040.1-2018 "Determination of tensile properties of plastics Part 1: General", and the results are shown in Table 2.

[0040] Table 2 Retention rate of elongation at break (%) Example 1 93.32 Example 2 95.14 Example 3 96.35 Comparative Example 1 91.47 Comparative Example 2 94.33 Comparative Example 3 81.42 It can be seen from the test results in Table 2 that Examples 2 and 3 of the present invention have more significant anti-ultraviolet performance. This is because UV-531 and UV-2908 in the formula can strongly absorb ultraviolet rays, and the scattering and absorption of ultraviolet rays by yttrium-doped zinc oxide or modified yttrium-doped zinc oxide further improves the ultraviolet shielding performance. The doping of yttrium and the presence of less agglomeration give the modified yttrium-doped zinc oxide stronger shielding performance for ultraviolet rays, which works together with UV-531 and UV-2908 in the formula, thereby significantly improving the anti-ultraviolet performance of the masterbatch.

[0041] The impact strength of the masterbatches of the embodiment and the comparative example was tested after being immersed in water for 20 days, and the impact strength retention rate was calculated. The results are shown in Table 3.

[0042] Table 3 Impact strength retention rate (%) Example 1 80.4 Example 2 89.1 Example 3 92.3 Comparative Example 1 83.3 Comparative Example 2 91.5 It can also be seen from the test results in Table 3 that the masterbatch prepared in Example 3 of the present invention also has excellent water resistance, which is due to the good compatibility of the modified yttrium-doped zinc oxide in PMMA resin.

[0043] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. Anti-UV masterbatch for road sign reflective film, characterized in that: In terms of mass percentage, it includes: 10%~20% yttrium-doped zinc oxide or modified yttrium-doped zinc oxide, 2%~5% dispersant, 2%~5% UV inhibitor, 0.5%~1% antioxidant, and the remainder is PMMA resin.

2. The UV-resistant masterbatch for road sign reflective film according to claim 1, characterized in that: The preparation method of yttrium-doped zinc oxide comprises, by weight, 2-5 parts of a soluble zinc salt, 0.1-0.3 parts of a soluble yttrium salt and 50-100 parts of a solvent are mixed, the pH is adjusted, and then a hydrothermal reaction is performed to obtain yttrium-doped zinc oxide.

3. The UV-resistant masterbatch for road sign reflective film according to claim 1, characterized in that: The preparation method of the modified yttrium-doped zinc oxide comprises, by parts by mass, 2-5 parts of soluble zinc salt, 0.1-0.3 parts of soluble yttrium salt, 0.5-1 parts of isoleucine and 50-100 parts of solvent are mixed, pH is adjusted, and then a hydrothermal reaction is performed to obtain modified yttrium-doped zinc oxide.

4. The UV-resistant masterbatch for road sign reflective film according to claim 3, characterized in that: When adding isoleucine, 0.1 to 0.3 parts of sodium benzoate are also added.

5. The UV-resistant masterbatch for road sign reflective film according to claim 2 or 3, characterized in that: The solvent includes at least one of water, ethanol, acetone, isopropanol and ethylene glycol.

6. The UV-resistant masterbatch for road sign reflective film according to claim 2 or 3, characterized in that: Adjust pH to 11.0-13.0; The hydrothermal reaction lasts for 8 to 12 hours at 130 to 180 °C.

7. The UV-resistant masterbatch for road sign reflective film according to claim 1, characterized in that: The dispersant includes at least one of polyethylene wax, diffusion oil, talcum powder and ammonium stearate.

8. The UV-resistant masterbatch for road sign reflective film according to claim 1, characterized in that: The anti-ultraviolet agent includes at least one of a benzophenone anti-ultraviolet agent, a hindered benzoate anti-ultraviolet agent, and a benzotriazole anti-ultraviolet agent.

9. The UV-resistant masterbatch for road sign reflective film according to claim 1, characterized in that: The antioxidant comprises at least one of a hindered phenol antioxidant and a phosphite antioxidant.

10. A method for preparing the anti-UV masterbatch for road sign reflective film according to any one of claims 1 to 9, characterized in that: include, The PMMA resin is heated and melted, and then yttrium-doped zinc oxide or modified yttrium-doped zinc oxide and a dispersant are added, mixed and stirred to obtain a mixture; Add an anti-ultraviolet agent and an antioxidant into the mixture, mix and stir, and then extrude and granulate to obtain an anti-UV masterbatch for road sign reflective film.

Citation Information

Patent Citations

  • High-transmittance aging-resistant PMMA color master batch and preparation method thereof

    CN110903587A

  • Micro-nano laminated PMMA / nano ZnO composite material and preparation method thereof

    CN116041883A